(untitled) (Andamios, Revista de Investigación Social, 2022)
The article proposes to discuss the scope of the moral discourse of the logic of cruelty in forced disappearances during the six-year administration of Felipe Calderón. It also seeks to identify practices that can reverse this grammar. To this end, two perspectives are used: a philosophical-anthropological one and a political-journalistic one, whose methodological structure posits four analytical axes. These include the ethical and moral distinction to determine what the logic of cruelty involves; a political-journalistic analysis to contextualize Calderón’s “war on drug trafficking,” a turning point in the increase in forced disappearances; the instrumentality of moral grammar and the logic of criminalization in the process of forced disappearance; and the ethical response of the “searchers” that points to the transgression of the logic of cruelty.